Beyond Tradition: Revolutionary Leadership in Academia - Ahmad, Abd Rahman; Md Sapry, Hairul Rizad (JBS Nexus, 2025)
This paper looks into the importance of leadership for encouraging new approaches and cultural changes in higher education institutions. In higher education, leaders help guide the organisation’s journey of transformation. Today, institutions need to be innovative and able to adapt to changing global, technological and social realities. This paper also reviews how leadership contributes to innovation by putting in place new programs and approaches that boost the institution’s success. It also investigates how leaders affect and sustain the personality of the organisation, making it easier for people to cooperate, depend on and trust one another and get better. Good leadership ensures that evolution matches the core beliefs of an institution. A well-defined culture can ensure that stakeholders are more positive and involved. It was found that strategies in higher education work best when leaders guide the vision, govern ethically, create new ideas and involve important parties in making the changes. Additionally, the study reveals that having good leaders is important for achieving success in institutions and colleges as well as maintaining their place in the current educational system. This study also highlights that transformational leadership relies on culture, and innovation is important for ensuring excellence, toughness and durability at institutions.